Análisis de contenido y nivel de audiencia de enlace visión canal 14 de Puebloviejo - Vivas Contreras, Gabriela Betzaida (2022)
In this research project, it is proposed to develop an analysis of the content and audience level of Enlace Vision Channel 14 of Puebloviejo. The research method to be used is the qualitative study since it is required to obtain information from texts, web documents and interviews with social communicators, which allows collecting the necessary data to meet the stated objective. The development of this project is justified, due to the importance and impact of audiovisual content for the community of Puebloviejo and surrounding sectors; It is relevant to consider the quality of programming, determine if it is appropriate both in the broadcast schedule and in the audience it is intended to reach. This is the only local channel in Puebloviejo, therefore, it is important to determine the quality of television content that is being provided to the television audience, in addition to analyzing the degree of local acceptance of the channel. The research aims to obtain relevant data such as: the level of consumption that local television has by the inhabitants of the canton, the importance they place on informative and cultural issues regarding the canton and its incidence; In addition to this, the predisposition on the part of those who make up the channel's board of directors to be able to know the current reception of the channel; and, if necessary, have a predisposition to forge changes in this regard.